Judicial Activism Or Constitutional Obligation: Study Of The Indian Supreme Court’s Guidance For Standards In Public Life - Shanmuganathan, D (Journal of Malaysian and Comparative Law, 2000)
Question: Are you taking steps to correct [corruption]? Answer: We are trying. I would not claim that we have succeeded. But one thing that is helping also is the independence of judiciary.